Nucleus accumbens shell modulates seizure propagation in a mouse temporal lobe epilepsy model - Zou, Wenjie; Guo, Zhipeng; Suo, Longge; Zhu, Jianping; He, Haiyang; Li, Xiufeng; Wang, Kewan; Chen, Rongqing (Frontiers in Cell and Developmental Biology, 2022)
Temporal lobe epilepsy (TLE) is the most common form of epilepsy with focal seizures which in some conditions can develop into secondarily generalized tonic-clonic seizures by the propagation of epileptic activities in the temporal lobe to other brain areas. Nucleus accumbens (NAc) has been suggested as a treatment target for TLE as accumulating evidences indicate that NAc, especially its shell, participates in the process of epileptic seizures of patients and animal models with TLE. The majority of neurons in the NAc are GABAergic medium spiny neurons (MSN) expressing dopamine receptor D1 (D1R) or dopamine receptor D2 (D2R). However, the direct evidences of the NAc shell participating in the propagation of TLE seizures is missing and its cell type-specific modulatory roles in TLE seizures are unknown. In this study, we microinjected kainic acid into basolateral amygdala (BLA) to make a mouse model of TLE with initial focal seizures and secondarily generalized seizures (SGSs). We found that TLE seizures caused robust c-fos expression in the NAc shell and increased neuronal excitability of D1R-expressing MSN (D1R-MSN) and D2R-expressing MSN (D2R-MSN). Pharmacological inhibition of the NAc shell alleviated TLE seizures by reducing number of SGSs and seizure stages. Cell-type-specific chemogenetic inhibition of either D1R-MSN or D2R-MSN showed similar effects with pharmacological inhibition of the NAc shell. Both pharmacological and cell-type-specific chemogenetic inhibition of the NAc shell did not alter the onset time of focal seizures. Collectively, these findings indicate that the NAc shell and its D1R-MSN or D2R-MSN mainly participate in the propagation and generalization of the TLE seizures.